COMPARING CARCASS END-POINT AND PROFIT MAXIMIZATION DECISION RULES USING DYNAMIC NONLINEAR GROWTH FUNCTIONS. (26th January 2015) - MAPLES, JOSHUA G.; COATNEY, KALYN T.; RILEY, JOHN M.; KARISCH, BRANDI B.; PARISH, JANE A.; VANN, RHONDA C.
Abstract This article develops a market timing decision rule for cattle feeders based on profit maximization. We then compare it with the "status quo" strategy of feeding cattle to a targeted carcass end point. We estimate individual nonlinear dynamic growth functions to derive each animal's value of the marginal product in relation to days on feed. Given individual marginal factor costs, our results indicate that the use of a profit maximization rule could have increased average profits by $16.56 to $21.09 per head for the cattle of known age, and $7.67 to $11.32 per head if age was unknown.